The Influence of Price and Promotion Perceptions on The Decision to Purchase Indosat Ooredoo Data Packages With Brand Image as an Intervening Variable - Humaidah, Siti Naelatul; Haerudin, Haerudin; Jumai, Jumai; Nurhayati, Nurhayati (Economics and Business International Conference Proceeding, 2024)
This research aims to analyze the influence of price and promotion perceptions on purchasing decisions for Indosat Ooredoo data packages with Brand Image as an intervening variable. This study involved 100 students from the 2020-2023 Bachelor of Management Study Program at Muhammadiyah University Semarang. The research method used is quantitative with data collection techniques using questionnaires, and the analytical tool used is Structural Equation Modeling - Partial Least Squares (SEM-PLS). The research results show that price perceptions do not directly have a significant effect on purchasing decisions, while promotions have a positive and significant effect. Apart from that, price perceptions and promotions have a significant effect on Brand Image, which then mediates the influence of both on purchasing decisions. The coefficient value shows that price perception and promotion contribute to Brand Image by 0.56 and 0.64 respectively, which then influences purchasing decisions with a coefficient value of 0.48. These findings imply that companies must pay attention to price and promotion factors as well as how Brand Image is formed to improve consumer purchasing decisions.